Real-Time Determination of Molecular Weight: Use of MaDDOSY (Mass Determination Diffusion Ordered Spectroscopy) to Monitor the Progress of Polymerization Reactions - Tooley, Owen; Pointer, William; Radmall, Rowan; Hall, Mia; Swift, Thomas; Town, James; Aydogan, Cansu; Junkers, Tanja; Wilson, Paul; Lester, Daniel; Haddleton, David (ACS polymers Au, 2024)
Knowledge of molecular weight is an integral factor in polymer synthesis, and while many synthetic strategies have been developed to help control this, determination of the final molecular weight is often only measured at the end of the reaction. Herein, we provide a technique for the online determination of polymer molecular weight using a universal, solvent-independent diffusion ordered spectroscopy (DOSY) calibration and evidence its use in a variety of polymerization reactions.